Digital Exposure in Early Childhood: Health Risks and Protective Strategies During Remote Learning. - Yelizarova, Olena; Stankevych, Tetiana; Parats, Alla; Yelizarov, Viktor; Puzanova, Olha; Lebedynets, Natalia; Hozak, Svitlana (Inquiry (00469580), 2025)
The rapid integration of digital technology in early childhood education has raised concerns about managing preschool screen time (ST) and its potential harm to children's health and development. These concerns intensify during crises like pandemics or conflicts, when remote learning becomes necessary. Identifying risk and protective factors related to digital exposure is essential for child well-being. To investigate health risks and protective strategies linked to ST among preschool children during remote learning. A literature review was conducted from 2010 to 2025 using scientometric databases. Studies on health effects of digital exposure in early childhood were included. The review was illustrated with findings from our study of 1312 parents of preschoolers aged 4 to 6, which explored the relationship between ST and mastery of learning programs. Excessive ST was associated with reduced physical activity, irregular sleep, emotional difficulties, and delayed language acquisition. Higher ST was also linked to lower odds of completing the preschool learning program. Effective protective strategies included structured routines, parental co-viewing, and limiting passive ST. Reducing parental technoference emerged as a protective factor. Contextual factors such as socioeconomic disparities and caregiver digital literacy influenced outcomes. Remote learning presents both challenges and opportunities for preschoolers. While excessive screen use and parental technoference can negatively impact health and learning, evidence-based strategies, such as co-viewing, regulated content, and mindful parental engagement, can help reduce harm. Developing health-informed digital practices in early education is critical in times of crisis.